Active ageing – perspectives on health, participation, and security among older adults in northeastern Thailand – a qualitative study - Wongsala, Manothai (BMC Geriatr, 2021)
BACKGROUND: Health, participation, and security are the basic pillars of active ageing suggested by the WHO. The concept is used by professionals but requires exploration from the perspectives of older people themselves. This study aims to explore how older adults experience and describe health, participation, and security. METHODS: A qualitative research approach was used based on open-ended interviews with 20 older Thai adults aged 60–92 years. The interviews were analysed using qualitative content analysis. RESULTS: The results showed perspectives related to experiences of daily life and local culture. Health while ageing, was described as the absence of barriers to continued daily living, combined with a peaceful and adaptive mindset. Participation was described as maintaining social networks and being a formal volunteer, with an emphasis on the “making of merits”, of meaningful activities and being respected. Security was described as manageable living conditions and managing to finalize life well by balancing dependency and independency in relation to children to sustain the traditional value of gratitude between generations. CONCLUSIONS: These understandings will support healthy policy planning by providing resources and activities that relate to older Thai adults’ perspectives of health, participation and security and ultimately contribute to a better quality of life. SUPPLEMENTARY INFORMATION: The online version contains supplementary material available at 10.1186/s12877-020-01981-2.